SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS TYPE 2 OMICRON VARIANT OUTBREAK IN INDIA: TIME TO ALERT - NAGARAJAN, PRITHIVIRAJ; KUMAR, JAYANTHI; HOWLADER, ANUSHEELA; SABAPATHY, SATHEESH KUMAR; GOPAL, MUTHU; PORT LOUIS, LEENA RAJATHY; KUMAR, SARAVANAAVEL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Early 2022 saw an outbreak of the coronavirus severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) variant known as Omicron, which has become more contagious than the previous variants of concern alpha, beta, and gamma variants, and it shares many mutations. Still, so far, Omicron transmission has exceeded many borders worldwide compared to other kinds of SARS-CoV-2; there has been a significant increase in the number of confirmed cases globally, and it is re-emerging currently in India. The World Health Organization, the Centers for Disease Control and Prevention (CDC), the Ministry of Health and Family Welfare, and other research institutions, as well as worldwide international press media provided data on “Omicron” outbreaks in India. Our review recorded information about the prevalence and clinical characteristics of the Omicron variant of SARS-CoV-2 from November 24, 2021, to January 17, 2022. Our highlights will talk about its global transmission, characteristics, and impact on vaccine efficiency, and possible strategies to prevent and overcome the spread of the Omicron variant.